Identification of a Rare Exon 19 Skipping Mutation in ALMS1 Gene in Alström Syndrome Patients From Two Unrelated Saudi Families - Saadah, Omar I.; Banaganapalli, Babajan; Kamal, Naglaa M.; Sahly, Ahmed N.; Alsufyani, Hadeel A.; Mohammed, Arif; Ahmad, Aftab; Nasser, Khalidah Khalid; Al-Aama, Jumana Y.; Shaik, Noor Ahmad; Elango, Ramu (Frontiers in Pediatrics, 2021)
Background: Alström syndrome (AS) is a very rare childhood disorder characterized by cardiomyopathy, progressive hearing loss and blindness. Inherited genetic variants of ALMS1 gene are the known molecular cause of this disease. The objective of this study was to characterize the genetic basis and understand the genotype–phenotype relationship in Saudi AS patients. Methods: Clinical phenotyping and whole-exome sequencing (WES) analysis were performed on six AS patients belonging to two unrelated consanguineous Saudi families. Sanger sequencing was performed to determine the mode of inheritance of ALMS1 variant in first-degree family relatives and also to ensure its rare prevalence in 100 healthy population controls. Results: We identified that Alström patients from both the families were sharing a very rare ALMS1, 3′-splice site acceptor (c.11873−2 A>T) variant, which skips entire exon-19 and shortens the protein by 80 amino acids. This disease variant was inherited by AS patients in autosomal recessive mode and is not yet reported in any population-specific genetic databases. AS patients carrying this mutation showed heterogeneity in clinical presentations. Computational analysis of the mutant centroid structure of ALMS1 mRNA revealed that exon-19 skipping enlarges the hairpin loop and decreases the free energy, eventually affecting its folding pattern, stability, and function. Hence, we propose c.11873–2A as an AS causative potential founder mutation in Saudi Arabia because it is found in two families lacking a common lineage. Conclusions: We conclude that WES analysis potentially helps in clinical phenotyping, early diagnosis, and better clinical management of Alström patients showing variable clinical expressivity.